Making the point? The audiovisual/digital media dissertation. (8th April 2014) - Houtman, Coral; Thomas, Maureen; Barrett, Jennifer
Abstract : Purpose: – The purpose of this paper is to address the advantages of education and training in creating the "Audiovisual/Digital Media Essay" (AV/DME), starting from visual and cinematic thinking as a way of setting up, developing and concluding an argument. Design/methodology/approach: – Recognising the advantages to education and training of the "AV/DME" this paper explores ways of enabling visually disciplined students to work on film theory within their chosen medium, and to develop arguments incorporating audiovisual sources, using appropriate academic skills. It describes a hands-on BA/MA workshop held at Newport Film School (May 2011) and subsequent initial implementation of an examinable DME. The paper contextualises the issue in the light of practice-led and practice-based research and of parity with written dissertations. Drawing on analysis of in-depth interviews with students and tutors, it makes practical recommendations for how to resource, staff and support the implementation and continuation of the AV/DME and/or dissertation. Findings: – The paper feeds back from both students and staff on the running of an initial AV/DME workshop and finds that the Film School Newport is suited to running the AV/DME and suggests a framework for its support. Research limitations/implications: – The study needs to be followed up when the students complete their full dissertations. Practical implications: – The AV/DME needs sufficient technical and human resources to support student learning. Originality/value: – The paper provides a clear and original framework for teaching, supporting and assessing the AV/DME. This framework can be disseminated beyond the University of Wales Newport, and can be used to teach the AV/DME in further contexts and to wider groups of students.